Interoception in Anorexia Nervosa: Exploring Associations With Alexithymia and Autistic Traits - Kinnaird, Emma; Stewart, Catherine; Tchanturia, Kate (Frontiers in Psychiatry, 2020)
Background: Previous research on whether interoception is altered in anorexia nervosa (AN) using the heartbeat tracking task has yielded inconsistent results. However, no previous research has examined whether interoception is associated with alexithymia and autistic traits in AN, conditions which are more prevalent in this population and thought to be related to performance in this task. The aim of this study was to explore whether altered interoception in AN is associated with alexithymia and autistic traits. Methods: We assessed interoceptive accuracy using the heartbeat tracking task in n=37 people with AN, and n=37 age and gender matched healthy controls (HC), and explored within the AN group if interoceptive accuracy was related to self-rated alexithymia or autistic traits. We also assessed self-reported interoceptive ability, and the relationship between subjective and actual performance. Results: Heartbeat tracking task performance was not found to be altered in the AN group compared to the HC group. However, confidence ratings in task performance in the AN group were lower compared to the HC group. Unlike the HC group, confidence ratings in the AN group did not correlate with task performance. Within the AN group there was no relationship between interoceptive accuracy, alexithymia, and autistic traits, after controlling for the potential confounders of anxiety and depression. There was a relationship between confidence ratings and illness severity in the AN group. Conclusion: The results found no differences between heartbeat tracking task performance in people with AN compared to HC. There was no association between task performance, alexithymia and autistic traits in AN. Results do suggest that people with AN exhibit lowered confidence in their task performance, and that they may lack insight into this performance compared to HC. The findings are discussed in the context of potential significant limitations of the heartbeat tracking task, with recommendations for future research into interoception in AN.